The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2174/1871526515666150724111528
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Drug Targets in Helicobacter pylori Strain HPAG1 by <i>in silico</i> Genome Analysis

Abstract: Helicobacter pylori colonizes the stomach, causing gastritis, peptic ulcers and gastric carcinoma. Drugs for treatment of H. pylori relieve from gastritis or pain but are not specific to H. pylori. Therefore, there is an immediate requirement for new therapeutic molecules to treat H. pylori. Current study investigates identification of drug targets in the strain HPAG1 of H. pylori by in silico genome analysis. Genome of HPAG1 was reconstructed for metabolic pathways and compared with Homosapien sapiens to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Some of them are detailed in Table 1, and the more relevant ones are described below. Coenzyme A biosynthesis [35,36] Carbon starvation protein A Starvation response, utilization of peptides, and host-pathogen interactions [37] Methylthiotransferase (MiaB) Protein synthesis [37] Ribosomal RNA small subunit methyltransferase E Protein synthesis [37] Ribosomal protein L11 methyltransferase Protein synthesis [37] Tetrapyrrole (Corrin-Porphyrin) methylase family protein Protein synthesis [37] Peptide chain release factor 1 Protein synthesis [37] Fumarate reductase (FrdA, FrdB, and FrdC)…”
Section: Targets For Hp Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them are detailed in Table 1, and the more relevant ones are described below. Coenzyme A biosynthesis [35,36] Carbon starvation protein A Starvation response, utilization of peptides, and host-pathogen interactions [37] Methylthiotransferase (MiaB) Protein synthesis [37] Ribosomal RNA small subunit methyltransferase E Protein synthesis [37] Ribosomal protein L11 methyltransferase Protein synthesis [37] Tetrapyrrole (Corrin-Porphyrin) methylase family protein Protein synthesis [37] Peptide chain release factor 1 Protein synthesis [37] Fumarate reductase (FrdA, FrdB, and FrdC)…”
Section: Targets For Hp Infectionmentioning
confidence: 99%
“…Krebs cycle and anaerobic respiration [33,38] Glu-tRNA Gln amidotransferase, subunits A (GatA), B (GatB), and C (GatC) Protein synthesis [26,33] Coenzyme A biosynthesis [35,36] Carbon starvation protein A Starvation response, utilization of peptides, and host-pathogen interactions [37] Methylthiotransferase (MiaB) Protein synthesis [37] Ribosomal RNA small subunit methyltransferase E Protein synthesis [37] Ribosomal protein L11 methyltransferase Protein synthesis [37] Tetrapyrrole (Corrin-Porphyrin) methylase family protein Protein synthesis [37] Peptide chain release factor 1 Protein synthesis [37] Fumarate reductase (FrdA, FrdB, and FrdC) Krebs cycle and anaerobic respiration [33,38] Glu-tRNA Gln amidotransferase, subunits A (GatA), B (GatB), and C (GatC) Protein synthesis [26,33] Helicase-nuclease DNA Repair Enzymes (AddAB) DNA damage reparation [39,40] Cytochrome C-type biogenesis protein CcdA Cytochrome C synthesis [37] Cytochrome C oxidase, subunits CcoN, CcoO, CcoP and CcoQ ATP synthesis [37] Flavodoxin (Fld) Oxidative decarboxylation of pyruvate [28,[41][42][43] Table 1. Cont.…”
Section: Targets For Hp Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present day drug discovery and development follows a very systematic and complex process to generate Food and Drug Administration (FDA) approved drugs. The drug discovery process starts with identification and validation of drug targets for a particular disease [1][2][3][4][5] . Medicinal chemists design a new molecule to the established target using Computer Assisted Drug Designing (CADD).…”
Section: Editorialmentioning
confidence: 99%
“…Yadav et al [7] showed the targetable virulence factors for pneumonia using bioinformatics tools. The other workers predicted drug targets for Helicobacter pylori using various in silico approaches [8,9]. Here, we have developed a new method for identification of drug target that is based on the already available drug targets.…”
Section: Introductionmentioning
confidence: 99%